2009
DOI: 10.1094/phyto-99-5-0506
|View full text |Cite
|
Sign up to set email alerts
|

Seed Treatment with 2,4-Diacetylphloroglucinol-Producing Pseudomonads Improves Crop Health in Low-pH Soils by Altering Patterns of Nutrient Uptake

Abstract: Seed treatment with a 2,4-diacetylphloroglucinol (DAPG)-producing Pseudomonas strain ameliorated abiotic stress disorder in corn caused by growth in a low-pH soil. In two consecutive growing seasons, Wood1R-treated seed gave rise to plants that grew taller (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…fluorescens strain. This was the first evidence that DAPG producers, in addition to their role in pathogen control, can also act to ameliorate abiotic stress factors (Raudales et al ., ). The presence of pollutants in soil has promoted the search for efficient bioremediation methods as an alternative for excavation and incineration.…”
Section: Impact Of the Rhizosphere Microbiome On Plant Growth Healthmentioning
confidence: 97%
“…fluorescens strain. This was the first evidence that DAPG producers, in addition to their role in pathogen control, can also act to ameliorate abiotic stress factors (Raudales et al ., ). The presence of pollutants in soil has promoted the search for efficient bioremediation methods as an alternative for excavation and incineration.…”
Section: Impact Of the Rhizosphere Microbiome On Plant Growth Healthmentioning
confidence: 97%
“…Recent studies have shown that different plant growth-promoting rhizobacteria (PGPR) can elicit so-called "induced systemic tolerance" to abiotic stresses, such as salt and drought (76) and acid soil stress (59). What role might volatiles play in these phenomena related to plant health?…”
Section: Production and Effects Of Bacterial Volatilesmentioning
confidence: 99%
“…Besides induction of resistance against pathogens, ROS play an important role in abiotic stresses such as drought and high salt (Mittler 2002). Recently accumulated studies presented that PGPR also augmented plant resistance to abiotic stresses referred to as "induced systemic tolerance" (Yang et al 2009b;Raudales et al 2009). More interestingly, among bacterial determinants, two recent studies demonstrated that bacterial volatiles conferred resistance to salt and drought (Zhang et al 2009b;Cho et al 2008).…”
Section: Enzymatic Activities Of Antioxidant Proteinsmentioning
confidence: 99%